Estimation of Health Effects attributed to PM 2.5 and Assessing the Health Quality of Semnan Air from the Perspective of this Pollutant - Kamyar Yaghmaeian; Safiyeh Ghobakhloo; Sajad Mazloomi (Mazandaran University of Medical Sciences, 2018)
Introduction and purpose: Urban outdoor air is contaminated with a variety of harmful agents that can lead to an increase in mortality and morbidity rate through short-term exposure. In recent studies conducted in Iran, the health effects of  suspended particles with a diameter of less than 2.5 micrometers (PM2.5) have been investigated and the results of many studies have proven the adverse effects of air pollutants on human health. The present study investigated the air quality and evaluated the health effects of PM2.5 on the residents of Semnan in 2017. Methods: The air quality index (AQI) introduced by the Environmental Protection Agency was used in order to evaluate the air quality. In addition, for the purpose of health effects evaluation AirQ software was utilized, which is proposed by the World Health Organization. It is worth mentioning that AQI was calculated by the interpolation between the concentration of the pollutants for PM2.5 and classified based on standard charts and tables. In AirQ software, the concentration of PM2.5 was utilized to assess human exposure and health effects in terms of the ratio attributable to the health implications, annual number of deaths for all causes, as well as cardiovascular and respiratory diseases. Results: According to the obtained results of this qualitative study, it was revealed that air quality has exceeded the standard level almost 18% (AQI>100); it was reported as unhealthy and dangerous in 6% and 2% of the days of the year, respectively. Based on the findings, the annual average of concentration was estimated as 18 μg/m3. Moreover, the maximum number of exposure days to PM 2.5 was related to the concentration of 13-25 μg/m3. Furthermore, more than 80% of the cardiovascular and respiratory mortalities, as well as the referrals of outpatients with respiratory and heart diseases, belonged to the same concentration class. Conclusion: Despite the limitations of using AirQ software (version 2.2.3) this method is an effective, easy, and helpful tool for decision-making.